2011
DOI: 10.1007/s11434-010-4280-3
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis of organic pollutant photodegradation by metal phthalocyanines immobilized on TiO2@SiO2

Abstract: A TiO 2 @SiO 2 hybrid support was prepared by the sol-precipitation method using n-octylamine as a template. The photocatalyst manganese phthalocyanine tetrasulfonic acid (MnPcS) was immobilized on the support to form MnPcS-TiO 2 @SiO 2 . X-ray diffraction (XRD) and UV-Visible diffuse reflectance spectra (UV-Vis DRS) were employed to characterize the catalyst. The photocatalytic degradation of rhodamine B (RhB) and the catalytic oxidation of o-phenylenediamine (OPDA) under visible light irradiation were used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…10−12 Metallophthalocyanines (MPcs) are able to absorb in visible light or sunlight, and have attracted high * Correspondence: sevim@itu.edu.tr interest for visible light-employing catalytic photodegradation of toxic industrial wastes. 13 The photoactivity of phthalocyanines comes from their ability to produce very reactive species such as hydroxyl radical (• OH) and singlet oxygen species ( 1 O 2 ) by photon flux absorption in the ultraviolet or visible part of the spectrum. In particular, in polar solvents, phthalocyanines show a tendency to form π -aggregates and the photocatalytic activity is reduced greatly, because aggregated metallophthalocyanines' excited energetic states are offset by nonexcited states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10−12 Metallophthalocyanines (MPcs) are able to absorb in visible light or sunlight, and have attracted high * Correspondence: sevim@itu.edu.tr interest for visible light-employing catalytic photodegradation of toxic industrial wastes. 13 The photoactivity of phthalocyanines comes from their ability to produce very reactive species such as hydroxyl radical (• OH) and singlet oxygen species ( 1 O 2 ) by photon flux absorption in the ultraviolet or visible part of the spectrum. In particular, in polar solvents, phthalocyanines show a tendency to form π -aggregates and the photocatalytic activity is reduced greatly, because aggregated metallophthalocyanines' excited energetic states are offset by nonexcited states.…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation inhibits ordering crystalline packing and localization of internal spaces. 13 Under these conditions, MPcs are dispersed and their photocatalytic activity is very effective.…”
Section: Introductionmentioning
confidence: 99%
“…Phthalocyanines can be one of the most efficient and stable class of photosensitizers for TiO 2 photocatalysts operating under visible light irradiation, as some studies have already reported [20][21][22][23][24][25][26][27][28][29], but the anchoring groups that could bind them on the nanoparticles surface [30] decisively determine the overall efficiency. Studies related to the stability of several coupling functionalities, such as carboxyl, phosphate, sulfonate, acetyl, silyl, hydroxyl, or amino reveal that carboxyl groups exhibit a very good stability during photocatalytic processes [31].…”
Section: Introductionmentioning
confidence: 99%
“…They tend to be lipid soluble and undergo food chain amplification and, if toxic, threaten human health. Advanced oxidation processes (AOPs) are among the best advanced treatment technologies because of their ability to mineralize organic pollutants [1,2].…”
mentioning
confidence: 99%
“…H 2 O 2 generated in situ is consumed prior to decomposition to H 2 O and O 2 , giving higher yields and selectivity for the targeted reactions. Although the classic Fenton reactions (Fe 2+ /H 2 O 2 ) have been widely used for the treatment of POPs, they have three main drawbacks: the high cost of H 2 O 2 , the large production of ferric hydroxide sludge and the narrow working pH range [2]. As iron ions precipitates as a hydroxide at higher pH values.…”
mentioning
confidence: 99%